Application of Computer-Aided Translation Technology in Translation Teaching - Erwen, Zhang; Wenming, Zhang (International Journal of Emerging Technologies in Learning (iJET), 2013)
this paper aims to advocate the application of CAT technology in the traditional translation teaching class in universities. Based on the introduction of the development of CAT technology and its wide application in modern translation industry, the necessity of applying CAT technology in translation teaching is convincingly proven, which is followed by an elaboration on the design of CAT teaching modules and the construction of CAT teaching system. At the end of this paper, a conclusion is made that only by applying CAT technology in translation teaching in universities, can the education of translation catch up with the development of the translation industry in this information age.